The Teams Games Tournament (TGT) Learning Model to Improve The Combination of Rhythmic Movements of Indonesian Students: A Systematic Literature Review - Yulia Ika; Mashud (S&Co Publishing, 2026)
The combination of rhythmic movements, especially in rhythmic gymnastics, requires the integration of movement coordination, musical rhythm, flexibility and body balance together. In this study, the TGT learning model offers advantages by encouraging students to learn and improve rhythmic movement combinations through enjoyable games and repetition. This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model in enhancing rhythmic movement combination skills and student learning outcomes in Indonesia. The research method used is a Systematic Literature Review (SLR) of relevant empirical studies based on predefined inclusion criteria. Articles were collected using the Google Scholar and CrossReff databases with the assistance of the Publish or Perish software, and the data were synthesized based on inclusion and exclusion criteria using the PICO approach. The population (P) consists of Indonesian students participating in rhythmic movement learning. The intervention (I) is the application of the TGT learning model, the comparison (C) is the conventional learning model, and the outcome (O) is the improvement in rhythmic movement. The synthesis of the reviewed studies shows that the application of TGT in the teaching of movement activities, such as rhythmic gymnastics and other rhythmic activities in Indonesia, consistently has a positive impact. The conclusion of this study is that the TGT learning model is an effective approach for optimizing students movement combination skills. Keywords: Teams Games Tournament, Rhytmic Activity, Physical Education